EFIKASI DIRI AKADEMIK PADA SISWA SEKOLAH MENENGAH PERTAMA DITINJAU DARI PERBEDAAN POLA ASUH ORANG TUA - Naisa Wanda Aska Arrianto; Aska Arrianto; Abdul Amin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Academic self-efficacy refers to students’ beliefs in their ability to complete academic tasks, cope with learning challenges, and meet academic demands. One of the factors that may influence academic self-efficacy is parenting style, as the family environment provides different levels of rules, support, supervision, and autonomy. This study aimed to examine differences in academic self-efficacy among junior high school students based on parental parenting styles. A comparative quantitative approach was employed in this study. The sample consisted of 275 students of SMP Negeri 2 Gempol selected from a population of 880 students using proportionate random sampling. The instruments used were an academic self-efficacy scale and a parenting style scale, both of which had been tested for validity and reliability. Data were analyzed through normality testing, homogeneity testing, one-way ANOVA, and Tukey’s HSD post hoc test. The results showed that the data were normally distributed and homogeneous. The one-way ANOVA test produced an F value of 6.783 with a significance value of 0.001, indicating a significant difference in students’ academic self-efficacy based on parenting styles. Furthermore, Tukey’s HSD test revealed a significant difference between authoritarian and permissive parenting styles, with a mean difference of 5.879 and a significance value of 0.001. Students who experienced authoritarian parenting demonstrated higher academic self-efficacy than those who experienced permissive parenting. This study concludes that parental structure, rules, supervision, and involvement play an important role in shaping students’ academic self-efficacy. ABSTRAK Efikasi diri akademik adalah keyakinan siswa terhadap kemampuannya dalam menyelesaikan tugas, menghadapi tantangan belajar, dan memenuhi tuntutan akademik. Salah satu faktor yang memengaruhi efikasi diri akademik adalah pola asuh orang tua, karena lingkungan keluarga memberikan aturan, dukungan, pengawasan, dan kebebasan yang berbeda. Penelitian ini bertujuan mengetahui perbedaan efikasi diri akademik siswa SMP berdasarkan jenis pola asuh orang tua. Penelitian menggunakan pendekatan kuantitatif komparatif dengan sampel 275 siswa SMP Negeri 2 Gempol dari 880 siswa, dipilih melalui teknik proportionate random sampling. Instrumen yang digunakan adalah skala efikasi diri akademik dan skala pola asuh orang tua yang telah teruji validitas dan reliabilitasnya. Analisis data meliputi uji normalitas, uji homogenitas, One Way ANOVA, dan uji lanjut Tukey HSD. Hasil penelitian menunjukkan data berdistribusi normal dan homogen. Uji One Way ANOVA menghasilkan nilai F sebesar 6,783 dengan signifikansi 0,001, menunjukkan terdapat perbedaan signifikan efikasi diri akademik siswa berdasarkan jenis pola asuh orang tua. Uji Tukey HSD menunjukkan perbedaan signifikan antara pola asuh otoriter dan permisif dengan mean difference sebesar 5,879 dan signifikansi 0,001. Siswa dengan pola asuh otoriter memiliki efikasi diri akademik lebih tinggi dibandingkan siswa dengan pola asuh permisif. Penelitian ini menyimpulkan bahwa struktur, aturan, pengawasan, dan keterlibatan orang tua berperan penting dalam membentuk efikasi diri akademik siswa.